Pertanggungjawaban Pidana terhadap Kurir Barang yang Diduga Melakukan Tindak Pidana Narkotika - Denisa Julita Pratiwi; Riska Andi Fitriono (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This study is motivated by the issue of criminalizing drug couriers, who in judicial practice are often equated with the main perpetrators, even though in reality they occupy a subordinate position in the drug distribution network. The lack of clarity in the differentiation of roles in Law No. 35 of 2009 on Narcotics has led to the application of criminal liability that tends to be formalistic and has the potential to disregard substantive justice. This study aims to analyze the form of criminal liability of Class I drug couriers and assess whether the Pekanbaru District Court Decision Number 119/Pid.Sus/2025/PN Pbr has reflected justice in the imposition of criminal penalties. The research method used is normative juridical with a legislative approach, case approach, and conceptual approach. The results of the study show that the criminal liability imposed on couriers in the verdict is direct as the main perpetrator, without considering the theory of the perpetrator's role, degree of fault, and the defendant's capacity to be held responsible. The judge emphasized the fulfillment of the elements of the act as formulated in Article 114 of Law Number 35 of 2009 concerning Narcotics, without adequate analysis of the mens rea and the factual contribution of the courier in the structure of the crime. Justice in this study is understood as substantive justice, which requires consistency between the punishment, role, and degree of fault of the perpetrator. Proportional punishment is interpreted as the imposition of sanctions that clearly distinguish between couriers as subordinate actors and the main actors who control the narcotics network. This study concludes that the criminal liability of narcotics couriers must be based on individualization of punishment and proportionality so that law enforcement not only fulfills legal certainty but also reflects substantive justice.